Pesticide Toxicity Profile: Triazine Pesticides - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of triazine pesticides registered for use in Florida.  This document is PI-121, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2006.